The clinical significance of in-house metagenomic next-generation sequencing for bronchoalveolar lavage fluid diagnostics in patients with lower respiratory tract infections - Li, Shixiao; Qin, Jiajia; Zhou, Peng; Peng, Minfei; Qian, Jiao; Cai, Yingying; Shi, Qingxin; Tung, Tao-Hsin; Shen, Bo; Yu, Sufei (Frontiers in Cellular and Infection Microbiology, 2022)
Objective Metagenomic next-generation sequencing (mNGS) technology has the potential to detect a wide range of pathogenic microorganisms. However, reports on the diagnostic value and clinical significance of different platforms of mNGS for patients with lower respiratory tract infections (LRTIs) remain scarce. Methods A total of 306 patients with suspected LRTIs were enrolled from January 2019 to December 2021. The diagnostic performance of conventional methods and mNGS on bronchoalveolar lavage fluid (BALF) were compared. BALF mNGS was performed using a commercial and an in-house laboratory. The diagnostic value and the clinical implications of mNGS for LRTIs were analyzed for the different platforms. Results The positive rate of mNGS in the in-house group was higher than that in the commercial group (85.26% vs. 70.67%, p < 0.001). mNGS significantly increased the pathogen detection rate compared with conventional methods [from 70.67% vs. 22.67% (p < 0.001) to 85.26% vs. 30.77% (p < 0.001)]. The pathogens detected using mNGS included bacteria, fungi, viruses, and atypical pathogens. The in-house platform performed well on a wider spectrum of microbial distribution. Furthermore, it showed an advantage in detecting mixed pathogens in immunocompromised patients. Among the mNGS positive cases, 34 (32.0%) cases had their antibiotics adjusted in the commercial group, while 51 (38.3%) cases had a change of treatment in the in-house group. Moreover, the turnaround time of mNGS and the time from mNGS to discharge in the in-house group were significantly shorter than those in the commercial group. Conclusion In-house mNGS had a higher detection rate and can show a wider spectrum of pathogens, with potential benefits for the clinic by shortening the turnaround time and hospitalization, and it may be more suitable for clinical microbiology laboratories.